Thermoplastic resin composition and thermoplastic resin composite body, and method for producing the same
A thermoplastic resin composition with controlled metal oxide particle size and ionic dispersant improves infrared absorption and visible light transmittance, addressing the issues of reduced performance in conventional composites.
Patent Information
- Application Number
- JP2023109967
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Conventional thermoplastic resin composites face issues with reduced infrared absorbing properties and visible light transmittance due to metal oxide aggregates, leading to compromised design and transparency.
A thermoplastic resin composition comprising a thermoplastic resin, a metal oxide with a particle size of 500 nm or less, and an ionic dispersant, which controls infrared and visible light transmittance, achieving a balance between infrared absorption/reflection and transparency.
The composition maintains high visible light transmittance (50% or more) while effectively absorbing or reflecting infrared rays, enhancing design and visibility.
Smart Images

Figure 2025008097000001 
Figure 2025008097000002 
Figure 2025008097000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition, a thermoplastic resin composite, and a method for producing the same. [Background technology]
[0002] In recent years, with the development of autonomous driving technology for automobiles, robots, drones, etc., the use of infrared rays has rapidly increased in various applications such as measuring distances, grasping shapes, and identifying objects. Materials used in such situations are required to have the property of absorbing or reflecting infrared rays, and the use of materials such as metals is increasing. In particular, in fields where weight reduction is important, traditional metal materials are being replaced by resin materials, and companies are actively developing materials using compound technology. In addition, from the perspective of material design and transparency (visibility), there is a growing need for resin materials that transmit visible light.
[0003] As a method for imparting the property of absorbing or reflecting infrared rays while maintaining the transparency of a resin material, for example, a method of dispersing a metal oxide such as tin oxide, indium oxide, or tungsten oxide in a resin can be mentioned. Patent Document 1 discloses a method of dispersing a stearic acid compound together with indium tin oxide in a thermoplastic resin. Patent Document 2 discloses a resin composition containing a polycarbonate resin, composite tungsten oxide microparticles, and an ultraviolet absorber having a benzoxazine skeleton. Patent Document 3 discloses a resin composition containing cesium-containing tungsten oxide microparticles surface-treated with an organic silane compound in a thermoplastic resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2000-234066 A [Patent Document 2] JP 2011-168636 A [Patent Document 3] JP 2016-017141 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, metal oxides have low dispersibility in thermoplastic resins, which leads to problems such as reduced infrared absorption due to aggregation and reduced visible light transmittance due to light scattering. Therefore, there is room for improvement in conventional techniques for obtaining thermoplastic resin composites with excellent design and transmittance (visibility).
[0006] The problem to be solved by the present invention is to provide a thermoplastic resin composite that absorbs or reflects infrared rays and has excellent transmittance (visibility) and design properties, a thermoplastic resin composition capable of providing such a composite, and a method for producing the same. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that by blending a thermoplastic resin (a), a metal oxide (b), and an ionic dispersant (c) as essential components and controlling the particle size of the metal oxide (b) to 500 nm or less, the ultraviolet and infrared transmittance of the resin composition can be adjusted, thereby providing a thermoplastic resin composite that solves the above problems, and have completed the present invention.
[0008] That is, the present disclosure provides a thermoplastic resin composition comprising a thermoplastic resin (a), a metal oxide (b), and an ionic dispersant (c) as essential components, 90% or more of the metal oxide (b) in the resin composition is present in a size of 500 nm or less, The average transmittance of infrared rays with wavelengths of 1000 to 2000 nm is 70% or less, The average transmittance of visible light having a wavelength of 400 nm to 700 nm is 50% or more, and The resin composition has an infrared transmittance / visible light transmittance ratio in the range of 0.3 to 0.9.
[0009] The present disclosure also relates to a thermoplastic resin film comprising a layer (A) made of the above-described thermoplastic resin composition, A layer (B) containing a thermoplastic resin (d), The average infrared transmittance of the layer (B) is 60% or more, The present invention relates to a thermoplastic resin composite having an average visible light transmittance of 50% or more.
[0010] The present disclosure also provides a method for producing a resin composition, comprising a step of blending a thermoplastic resin (a), a metal oxide (b) and an ionic dispersant (c) as essential components, and melt-kneading the mixture at a temperature equal to or higher than the melting point of the thermoplastic resin (a), 90% or more of the metal oxide (b) in the resin composition is present in a size of 500 nm or less, The average transmittance of infrared rays with wavelengths of 1000 to 2000 nm is 70% or less, The average transmittance of visible light having a wavelength of 400 nm to 700 nm is 50% or more, and The present invention relates to a method for producing a thermoplastic resin composition having an infrared transmittance / visible light transmittance in the range of 0.3 to 0.9.
[0011] The present disclosure also provides a method for producing a thermoplastic resin composite, comprising a step of melt-molding a resin composition, A layer (A) made of a thermoplastic resin composition produced by the method described above; A layer (B) containing a thermoplastic resin (d), The layer (B) has an average infrared transmittance of 60% or more, The present invention relates to a method for producing a thermoplastic resin composite having an average visible light transmittance of 50% or more.
[0012] The present disclosure also relates to filaments, staples, nonwoven fabrics, hollow fibers, and films made of the above-described thermoplastic resin composite.
[0013] The present disclosure also relates to methods of using the above-described filaments, staples, nonwoven fabrics, hollow fibers, and films in swimwear, underwear, fitness wear, protective clothing, fabrics, tents, tarps, umbrellas, and lenses.
[0014] The present disclosure also relates to a molded article obtained by melt molding the above-described resin composition.
[0015] The present disclosure also provides a method for producing a molded article, comprising the steps of producing a thermoplastic resin composition by the method described above, and melt-molding the obtained resin composition. Effect of the Invention
[0016] According to the present invention, it is possible to provide a thermoplastic resin composite that absorbs or reflects infrared rays and has excellent transmittance (visibility) and design properties, a thermoplastic resin composition capable of providing such a composite, and a method for producing the same.
[0017] In the present disclosure, light with a wavelength of 1000 to 2000 nm is referred to as infrared light, and light with a wavelength of 400 nm to 700 nm is referred to as visible light.
[0018] In the present disclosure, the transmittance (visibility) of a thermoplastic resin composite refers to the transmittance of visible light through the thermoplastic resin composite and the visibility of objects present through the thermoplastic resin composite. When the transmittance is improved, the visibility is also improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] An embodiment of the present disclosure will be described in detail below, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made without departing from the spirit of the present disclosure. In addition, when multiple upper and lower limit values are described for a specific parameter, any upper and lower limit values can be combined to form a suitable numerical range.
[0020] <Thermoplastic resin composition> The resin composition according to the present embodiment is characterized in that it contains a thermoplastic resin (a), a metal oxide (b) and an ionic dispersant (c) as essential components, the dispersion diameter of the metal oxide (b) being 500 nm or less, the average infrared transmittance being 70% or less, the average visible light transmittance being 50% or more, and the infrared transmittance / visible light transmittance being in the range of 0.3 to 0.9. The details are described below.
[0021] Thermoplastic resin (a) The thermoplastic resin composition according to this embodiment contains a thermoplastic resin (a) as an essential component.
[0022] The thermoplastic resin used in the present invention is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include polyolefin resins, polycarbonate resins, polystyrene resins, acrylic resins, polyoxymethylene resins, polyester resins, vinyl chloride resins, cycloolefin polymers (COP), and thermoplastic elastomers. The thermoplastic resin used in the present invention may be one type or a mixture of two or more types. When two or more types are mixed, it is preferable to use a combination of resins that are highly compatible with each other.
[0023] The polyolefin resin is a polyolefin resin obtained by polymerizing at least one kind of olefin, and may be a homopolymer or a copolymer. Examples of such olefins include α-olefins having 4 to 12 carbon atoms, including ethylene, propylene, isobutylene, and isobutene (1-butene), butadiene, isoprene, (meth)acrylic acid esters, (meth)acrylic acid, (meth)acrylamide, vinyl alcohol, vinyl acetate, vinyl chloride, styrene, and acrylonitrile.
[0024] Examples of the α-olefins having 4 to 12 carbon atoms include 1-butene, 2-methyl-1-propene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, and dimethyl 1-pentene, ethyl-1-pentene, trimethyl-1-butene, methylethyl-1-butene, 1-octene, methyl-1-pentene, ethyl-1-hexene, dimethyl-1-hexene, propyl-1-heptene, methylethyl-1-heptene, trimethyl-1-pentene, propyl-1-pentene, diethyl-1-butene, 1-nonene, 1-decene, 1-undecene, and 1-dodecene.
[0025] The polyolefin resin is not particularly limited, but examples thereof include polyethylene resin, polypropylene resin, polymethylpentene resin, polyisobutylene resin, polyisobutene resin, polyisoprene resin, polybutadiene resin, etc. Among these resins, polyethylene resin, polypropylene resin, and polymethylpentene resin are preferred.
[0026] When classified by density or shape, examples include high density polyethylene (HDPE), low density polyethylene (LDPE), very low density polyethylene (VLDPE), linear low density polyethylene (LLDPE), and ultra-high molecular weight polyethylene (UHMW-PE), of which high density polyethylene, linear low density polyethylene, and low density polyethylene are preferred.
[0027] Examples of polycarbonate resins include polycarbonate (PC), etc. Examples of polystyrene resins include polystyrene (PS), imide-modified polystyrene, acrylonitrile-butadiene-styrene (ABS) resin, imide-modified ABS resin, styrene-acrylonitrile copolymer (SAN) resin, and acrylonitrile-ethylene-propylene-diene-styrene (AES) resin.
[0028] Examples of acrylic resins include polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polymethyl methacrylate (PMMA), polyethyl methacrylate, etc. Examples of polyoxymethylene resins include polyoxymethylene (POM), etc. Examples of polyester resins include aromatic polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), and polybutylene naphthalate.
[0029] Examples of vinyl chloride resins include polyvinyl chloride (PVC), vinyl chloride-vinyl acetate copolymer resin, etc. Examples of thermoplastic elastomers include polyurethane thermoplastic elastomers, polyester thermoplastic elastomers, styrene thermoplastic elastomers, olefin thermoplastic elastomers, etc.
[0030] From the viewpoint of transparency, the thermoplastic resin (a) is preferably at least one selected from the group consisting of polyolefins, polyamides, polyesters, polyarylene sulfides, and polycarbonates.
[0031] In the resin composition according to the present embodiment, the blending amount of the thermoplastic resin (a) is not particularly limited, but is preferably 50 parts by mass or more, more preferably 99.99 parts by mass or less, and more preferably 99.95 parts by mass or less, more preferably 99.90 parts by mass or less, relative to 100 parts by mass of the resin composition. If the blending amount does not satisfy the above range, the processability and infrared wavelength controllability become poor.
[0032] Metal oxides (b) The thermoplastic resin composition according to this embodiment contains a metal oxide (b) as an essential component for the purpose of controlling the infrared transmittance.
[0033] The metal oxide (b) applicable to this embodiment may be any known or used metal oxide as long as it does not impair the effects of the present invention. From the viewpoint of visible light transmittance, it is preferably made of an oxide semiconductor, and more preferably an oxide semiconductor containing at least one selected from the group consisting of molybdenum, nickel, indium, zinc, tin, titanium, vanadium, tungsten, strontium, and antimony.
[0034] The amount of the metal oxide (b) is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 0.01 parts by mass or more, more preferably 100 parts by mass or less, and more preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin (a). If it is less than this range, excellent infrared controllability cannot be exhibited, and if it exceeds this range, visible light transmittance may deteriorate.
[0035] In the resin composition according to the present embodiment, the metal oxide (b) preferably has a particle diameter of 500 nm or less from the viewpoint of maintaining the transparency of the resin composition and the molded article. In this range, the metal oxide (b) does not completely block visible light due to scattering, and can maintain the transparency in the visible light region while efficiently maintaining the transparency. From the viewpoint of further improving the transmittance of visible light, the dispersion diameter is more preferably 200 nm or less, and even more preferably 100 nm or less. The dispersion particle diameter of the metal oxide can be measured by observing the cross section of the resin composition with a scanning electron microscope and measuring the particles.
[0036] The reason why the particle size of the metal oxide (b) affects the visible light transmittance of the resin composition and the molded article is presumed to be due to the following mechanism. First, it is known that particles smaller than 800 nm do not completely block visible light due to scattering and maintain the transparency of the visible light region. When the metal oxide (b) is dispersed in the thermoplastic resin (a) with such a particle size, the transparency of the resulting resin composition and molded article can be maintained. It is also known that if the particle size of the particles is smaller, the scattering of visible light due to geometric scattering or Mie scattering is suppressed, so that the haze value of the resin composition and the molded article is smaller and the transparency can be maintained more. For example, when the particle size is 200 nm or less, the geometric scattering or Mie scattering is reduced to the Rayleigh scattering region, so that the shielding of visible light due to scattering is significantly reduced. Note that the above mechanism is merely presumed, and even if the effect of the present invention is achieved for other reasons, it is included in the technical scope of the present invention.
[0037] ·Ionic dispersants (c) The thermoplastic resin composition according to this embodiment contains an ionic dispersant (c) as an essential component for the purpose of improving the dispersibility of the metal oxide (b). The ionic dispersant (c) applicable to this embodiment is not particularly limited as long as it does not impair the effects of the present invention, and any known dispersant having an ionic functional group in its structure can be used. The ionic functional group may be an anion or a cation, or may have both in its structure.
[0038] Examples of the ionic functional group include anionic groups such as sulfate, sulfonate, carboxylate, and phosphate groups, ammonium groups such as primary ammonium groups (ammonium groups), secondary ammonium groups (alkylammonium groups, etc.), tertiary ammonium groups (dialkylammonium groups, etc.), and quaternary ammonium groups (trialkylammonium groups, etc.), and cationic groups such as iminium groups, sulfonium groups, and phosphonium groups. Of these, at least one type may be included, and two or more types may be included. In particular, those having an anionic group are preferred, and those having a carboxylate group or a phosphate group are more preferred from the viewpoint of dispersibility.
[0039] Examples of commercially available ionic dispersants (c) include "ADEKACOL EC-8600" manufactured by ADEKA CORPORATION, "SN-PW-43" manufactured by SAN NOPCO LTD., "EMAL 20T" manufactured by Kao Corporation, "Phosphanol RS-610" manufactured by Toho Chemical Industry Co., Ltd., "Kachiogen TML" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and "ADEKA AMPHORTH PB-30L" manufactured by ADEKA CORPORATION.
[0040] The properties of the ionic dispersant (c) are not particularly limited as long as they do not impair the effects of the present invention, but from the viewpoint of dispersibility and processability, for example, the weight average molecular weight (Mw) is preferably 20000 or less, more preferably 15000 or less. The weight average molecular weight in the present disclosure is a value measured using gel permeation chromatography.
[0041] Other Ingredients In addition to the above essential components, the thermoplastic resin composition according to the present embodiment may further contain optional components as appropriate depending on the application. For example, known and commonly used additives such as fillers, pigments, dyes, colorants, antistatic agents, antioxidants, heat stabilizers, UV stabilizers, UV absorbers, foaming agents, lubricants, flame retardants, flame retardant assistants, rust inhibitors, antiviral agents, and release agents may be added as optional components as necessary. These additives are not essential components, and may be used in an amount of, for example, preferably 0.01 parts by mass or more relative to 100 parts by mass of the thermoplastic resin (a), and preferably 1000 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 10 parts by mass or less, depending on the purpose and application so as not to impair the effects of the present invention.
[0042] The thermoplastic resin composition according to the present embodiment has an average infrared transmittance of 70% or less, an average visible light transmittance of 50% or more, and an infrared transmittance / visible light transmittance ratio in the range of 0.3 to 0.9. When the average infrared transmittance of the thermoplastic resin composition is 70% or less, the infrared shielding property of the resin composition can be improved, and when the average visible light transmittance is 50% or more, the resin composition can exhibit excellent visibility through the molded product of the resin composition due to excellent transparency. In addition, when the infrared transmittance / visible light transmittance ratio is in the range of 0.3 or more to 0.9 or less, the infrared wavelength is shielded while the visibility is excellent. The average infrared and visible light transmittance of the resin composition in the present disclosure can be measured by the method described in the examples.
[0043] <Method of producing resin composition> The method for producing a thermoplastic resin composition according to the present embodiment is a method for producing a resin composition comprising a step of blending a thermoplastic resin (a), a metal oxide (b) and an ionic dispersant (c) as essential components, and melt-kneading the mixture at a temperature equal to or higher than the melting point of the thermoplastic resin (a), and is characterized in that the dispersion diameter of the metal oxide (b) is 500 nm or less, the average infrared transmittance is 70% or less, the average visible light transmittance is 50% or more, and the infrared transmittance / visible light transmittance is in the range of 0.3 to 0.9. The method will be described in detail below.
[0044] The method for producing the resin composition used in the present disclosure is not particularly limited, but includes a method of blending essential components and optional components as necessary, and melt-kneading, more specifically, a method of uniformly dry-mixing the components as necessary using a tumbler or Henschel mixer, and then feeding the components into a twin-screw extruder and melt-kneading them. In addition, kneaders such as a single-screw extruder, kneader, and Banbury mixer can also be used, and among them, a twin-screw extruder is preferred because it can be kneaded continuously.
[0045] The melt kneading can be carried out by heating to a temperature range in which the resin temperature is equal to or higher than the melting point of the thermoplastic resin (a), preferably equal to or higher than the melting point + 10° C., more preferably equal to or higher than the melting point + 10° C., even more preferably equal to or higher than the melting point + 20° C., to preferably equal to or lower than the melting point + 100° C., more preferably equal to or lower than the melting point + 50° C. Within this range, it becomes easy to disperse the inorganic compound in the thermoplastic resin, and thermal deterioration of each component can be suppressed.
[0046] The melt kneader is preferably a twin-screw kneading extruder from the viewpoint of dispersibility and productivity. For example, it is preferable to melt knead while appropriately adjusting the resin component discharge amount in the range of 5 to 500 (kg / hr) and the screw rotation speed in the range of 50 to 500 (rpm), and it is more preferable to melt knead under the condition that the ratio (discharge amount / screw rotation speed) is in the range of 0.02 to 5 (kg / hr / rpm). In addition, each component may be added and mixed to the melt kneader simultaneously or in portions. For example, when an optional component such as a filler is added as necessary, it is preferable to feed the component into the twin-screw kneading extruder from a side feeder from the viewpoint of dispersibility. The position of the side feeder is preferably such that the ratio of the distance from the extruder resin input part (top feeder) to the side feeder to the total screw length of the twin-screw kneading extruder is 0.1 or more, more preferably 0.3 or more. In addition, such a ratio is preferably 0.9 or less, more preferably 0.7 or less.
[0047] The thermoplastic resin composition according to the present disclosure obtained by melt kneading in this manner is a molten mixture containing the essential components, optional components added as necessary, and components derived therefrom. Therefore, the thermoplastic resin composition according to the present disclosure has a morphology of a sea-island structure in which the thermoplastic resin (a) forms a continuous phase and island phases containing the metal oxide (b), the ionic dispersant (c), and the optional components are dispersed.
[0048] After the melt kneading, the thermoplastic resin composition according to the present disclosure is preferably processed into a form such as pellets, chips, granules, powder, or the like by a known method, for example, by extruding the molten resin composition into a strand shape, and then pre-dried at a temperature range of 80 to 200°C as necessary.
[0049] <Thermoplastic resin composite> The thermoplastic resin composite according to this embodiment includes a layer (A) made of the above-described thermoplastic resin composition and a layer (B) containing a thermoplastic resin (d), and is characterized in that the average infrared transmittance of the layer (B) is 60% or less and the average visible light transmittance is 50% or more. The composite may have a two-layer structure or a repeating structure (e.g., layer A-layer B, layer A-layer B-layer A, layer A-layer B-layer A-layer B-layer A, layer B-layer A-layer B, etc.).
[0050] ·Layer (A) The thermoplastic resin composite according to this embodiment has, as an essential component, a layer (A) made of the above-described thermoplastic resin composition. The layer (A) transmits visible light and absorbs or reflects infrared light, and specifically, has an average visible light transmittance of 50% or more and an average infrared light transmittance of 70% or less.
[0051] ·Layer (B) The thermoplastic resin composite according to this embodiment further includes a layer (B) containing a thermoplastic resin (d) as an essential component. The layer (B) transmits both visible light and infrared light, and specifically, has an average infrared transmittance of 60% or more and an average visible light transmittance of 50% or more.
[0052] ·Thermoplastic resin (d) The thermoplastic resin (d) applicable to this embodiment is not particularly limited as long as it does not impair the effects of the present invention, and the same resin as the above-mentioned thermoplastic resin (a) can be used. In the thermoplastic resin composite according to this embodiment, the amount of the thermoplastic resin (d) blended in the layer (B) is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 100 parts by mass or less, and more preferably 50 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass of the layer (B). If such a range is not satisfied, the processability and interface adhesion will be poor.
[0053] In the thermoplastic resin composite according to the present embodiment, in addition to the above essential components, the layer (B) may further contain optional components as appropriate depending on the application. For example, known and commonly used additives such as fillers, pigments, dyes, colorants, antistatic agents, antioxidants, heat stabilizers, UV stabilizers, UV absorbers, foaming agents, lubricants, flame retardants, flame retardant assistants, rust inhibitors, antiviral agents, and release agents may be blended as optional components as necessary. These additives are not essential components, and may be used in an amount of, for example, preferably 0.01 parts by mass or more relative to 100 parts by mass of the thermoplastic resin (d), and preferably 1000 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 10 parts by mass or less, depending on the purpose and application so as not to impair the effects of the present invention.
[0054] <Method of manufacturing thermoplastic resin composite> The method for producing a thermoplastic resin composite according to the present embodiment is a method for producing a thermoplastic resin composite having a step of melt-molding a resin composition, The present invention relates to a method for producing a thermoplastic resin composite comprising a layer (A) made of the thermoplastic resin composition produced by the method described above, and a layer (B) containing a thermoplastic resin (d).
[0055] The method for producing the thermoplastic resin composite according to this embodiment is not particularly limited, and examples thereof include a method for producing the thermoplastic resin composite by co-extrusion molding the resin composition produced by the method described above and a thermoplastic resin, and a method for producing the thermoplastic resin composite by laminating the layer (A) and the layer (B) that have been produced, respectively.
[0056] The method of coextrusion molding is not particularly limited and can be carried out according to a conventional method, but examples include a coextrusion method in which the resins or resin mixtures used for each layer are heated and melted in separate extruders, laminated in a molten state by a coextrusion multilayer die method, a feed block method, or the like, and then formed into a film by an inflation method, a T-die chill roll method, or the like, or similarly laminated and then formed into a fiber by composite spinning, etc. This coextrusion method is preferable because it allows relatively free adjustment of the thickness ratio of each layer and can produce films and fibers with excellent cost performance.
[0057] In addition, when laminating the layer (A) and the layer (B), a known method can be used, such as a dry lamination method, a thermal lamination method, a multi-layer extrusion coating method, etc., and among these, the dry lamination method is more preferable. In addition, an adhesive can be used when laminating the layer (A) and the layer (B) in the dry lamination method. Examples of the adhesive that can be used include a polyether-polyurethane adhesive, a polyester-polyurethane adhesive, etc.
[0058] <Molded products> The resin composition and thermoplastic resin composite according to the present embodiment can be molded or processed into a shape according to the intended use. For example, it can be suitably used for applications such as films, sheets, fibers, tubes, etc., and can also be laminated to form a multi-layer film or sheet by laminating a plurality of films or sheets, or can be made into a fabric by weaving fibers, and further, known molding methods such as injection molding, compression molding, extrusion molding, pultrusion molding, blow molding, and transfer molding can be applied.
[0059] The form of the fabric may be, for example, any of woven fabric, knitted fabric, nonwoven fabric, etc. Furthermore, if necessary, the fabric may be colored with disperse dyes, acid dyes, direct dyes, reactive dyes, pigments, etc. The fabric of the present invention can be used for various textile products, such as clothing for general use, innerwear, sports, medical use, etc., bedding materials such as futon covers and sheets, interior goods such as curtains, carpets, chairs, cushion covers, wallpaper, etc., industrial materials such as tent sheets, flags, curtains, etc., sheet materials for transport vehicles such as automobiles, aircraft, and railway vehicles, sanitary materials, textile materials for air treatment, textile materials for water treatment, etc.
[0060] When the resin composition and thermoplastic resin composite according to the present embodiment are made into a nonwoven fabric, the fibers formed from the molten resin after melt kneading can be accumulated on a net to form a nonwoven fabric. The nonwoven fabric-like thermoplastic resin molded product may be molded through a post-treatment such as binding the fibers together with a binder or entangling the fibers together by applying an external force.
[0061] When the resin composition and thermoplastic resin composite according to the present embodiment are made into a thread (filament, staple, hollow fiber), the molten resin can be extruded from one or more holes having a predetermined cross-sectional shape after melt kneading to make the thread. The thread-shaped thermoplastic resin molded product may be further molded through post-treatments such as drawing, heat treatment, and twisting, or may be mixed with other yarns and spun to form a blended yarn or a blended fiber yarn.
[0062] The diameter (number average fiber diameter) of the fibers obtained by melt spinning the resin composition and thermoplastic resin composite according to the present embodiment varies depending on the application and can be any diameter, but since a smaller fiber diameter has better antiviral activity, it is preferably 100 μm or less, more preferably 40 μm or less, even more preferably 20 μm or less, and particularly preferably 10 μm or less, and the lower limit is not limited, but is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 1 μm or more. The fiber length is also not limited, and may be a long fiber length, so-called filament (long fiber), or a short fiber length, so-called staple (short fiber).
[0063] When the resin composition and thermoplastic resin composite according to the present embodiment are formed into a film, the molten resin can be extruded from a slit-shaped hole after melt kneading to form a film. The film-shaped thermoplastic resin molded product may be further molded by a press molding method or a vacuum molding method, or may be formed on a base layer to form a multilayer film.
[0064] In addition, the thickness of the sheet or film obtained by molding the resin composition and thermoplastic resin composite according to this embodiment into a sheet or film shape varies depending on the application, and can be any thickness, but is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 5 μm or more, particularly preferably 10 μm or more, and preferably 200 μm or less, more preferably 150 μm or less. The term sheet or film in the present invention is not intended to strictly distinguish between sheets and films, but is used to clarify that both are included, and as long as it has the characteristics of the present invention, the sheets and films can be interpreted as broadly as possible, and the term sheet includes what is called a plate or plate as long as it has the characteristics of the present invention. Even so, when it is necessary to distinguish between sheets and films, in the above range, the sheet is usually used when its thickness exceeds about 0.5 mm, and the film is usually used when its thickness is up to about 500 μm.
[0065] <Application> The thermoplastic resin composition of the present disclosure has visible light transmittance, and by controlling the transmittance of a specific wavelength in the infrared region, the resulting thermoplastic resin composite has excellent transmittance (visibility) and design, and is therefore particularly suitable for display materials, security applications, and fabrics. Specifically, it can be suitably used for light-cutting films for displays, tent fabrics, sportswear, and further infrared noise removal members. The thermoplastic resin composition and thermoplastic resin composite of the present disclosure are not limited to these, and can also be used in a wide range of applications. EXAMPLES
[0066] The present invention will be described below using examples and comparative examples, but is not limited to these examples. In the following, unless otherwise specified, "%" and "parts" are based on mass.
[0067] <Evaluation>
[0068] (1) Evaluation of the dispersion state of metal oxides The pellets of the compounds obtained in each of the Examples and Comparative Examples were cut using an ultramicrotome to obtain smooth cross sections. The cross sections were observed using a scanning electron microscope to measure the particle sizes. Four images of 10 μm squares were taken, and the proportion of particles of 500 nm or more was measured. The results are shown in Tables 1 to 3. [Evaluation Criteria] Particles smaller than 500 nm ○: Over 99%, very good. △: 90% or more, less than 99%, good. ×: Less than 90%, defective. It was rated as follows:
[0069] (2) Transmittance measurement A film having a thickness of 100 μm was prepared from each compound obtained in each Example and Comparative Example to be used as a test piece, and the average total light transmittance at each wavelength was measured in accordance with JIS K 7375 using a spectrophotometer UV-3100 manufactured by Shimadzu Corporation. The average transmittance at 400 to 700 nm in each test piece was taken as the visible light transmittance (%), and the average transmittance at 1000 to 2000 nm was taken as the infrared transmittance (%), and the infrared transmittance / visible light transmittance was calculated. The results are shown in Tables 1 to 3.
[0070] (3) Aggregation evaluation Using a single-screw extruder with a cylinder diameter of 25 mm and a wire mesh with 10 μm openings attached to the tip and set at a predetermined temperature, 1 kg of the compound obtained in each Example and Comparative Example was extruded. If the particles in the compound are not sufficiently dispersed, the wire mesh will become clogged with extrusion. Therefore, the difference between the pressure applied to the wire mesh at the beginning of extrusion and the pressure applied to the wire mesh when 1 kg of the compound is extruded (pressure increase value at the tip of the extruder) was calculated to evaluate the dispersion state. The results are shown in Tables 1 to 3. The smaller the value, the better the dispersibility. The dispersibility was evaluated according to the following criteria. It is preferably less than 5.0 MPa, more preferably less than 3.0 MPa, and even more preferably less than 1.0. The evaluation criteria △ and ○ are practical levels. [Evaluation Criteria] ○: Less than 1.0 MPa. Very good. △: 1.0 MPa or more and less than 5.0 MPa. Good. ×: 5.0 MPa or more. Not practical.
[0071] Example 1 100 parts by mass of low-density polyethylene (manufactured by Tosoh Corporation: "Petrothene (registered trademark) 202"), 0.5 parts by mass of gallium-doped zinc oxide (manufactured by Hakusui Tech Co., Ltd.: "Pazet GK", average particle size 30 nm), and 0.5 parts by mass of dispersant A (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.: "Plysurf (registered trademark) A208B", Mw2000, phosphate ester group-containing dispersant) were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200 ° C., mesh filter with supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (1). The obtained compound (1) was melt-cast using a 150 mm wide T-die extruder at an extrusion temperature of 180 ° C. to obtain an unstretched film (1) for transmittance measurement. Spectroscopic measurement of the obtained film (1) showed that the average transmittance in the visible light region was 70%, the average transmittance in the near infrared region was 62%, and the infrared transmittance / visible light transmittance was 0.9. The obtained compound was evaluated for aggregates and was evaluated for dispersion state, which was also good.
[0072] Example 2 100 parts by mass of low-density polyethylene, 0.5 parts by mass of cesium-doped tungsten oxide (manufactured by Lumi-M: cesium tungsten oxide, average particle size 30 nm), and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200 ° C., mesh filter with supplementary particle size 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (2). The obtained compound (2) was melt-formed into a film at an extrusion temperature of 180 ° C. using a 150 mm wide T-die extruder to obtain an unstretched film (2) for transmittance measurement. Spectroscopic measurement of the obtained film (2) showed that the average transmittance in the visible light region was 66%, the average transmittance in the near infrared region was 37%, and the infrared transmittance / visible light transmittance was 0.60.6. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0073] Example 3 100 parts by mass of low-density polyethylene, 0.5 parts by mass of tin-doped indium oxide (Mitsubishi Materials Corporation: ITO, average particle size 30 nm), and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200 ° C., mesh filter with supplementary particle size 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (3). The obtained compound (3) was melt-formed into a film at an extrusion temperature of 180 ° C. using a 150 mm wide T-die extruder to obtain an unstretched film (3) for transmittance measurement. Spectroscopic measurement of the obtained film (3) showed that the average transmittance in the visible light region was 80%, the average transmittance in the near infrared region was 60%, and the infrared transmittance / visible light transmittance was 0.80.8. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0074] Example 4 100 parts by mass of low-density polyethylene, 0.5 parts by mass of antimony-doped tin oxide (manufactured by Ishihara Sangyo Kaisha, Ltd.: "SN-100P", average particle size 30 nm), and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (4). The obtained compound (4) was melt-formed into a film at an extrusion temperature of 180°C using a 150 mm wide T-die extruder to obtain an unstretched film (4) for transmittance measurement. Spectroscopic measurement of the obtained film (4) showed that the average transmittance in the visible light region was 76%, the average transmittance in the near infrared region was 56%, and the infrared transmittance / visible light transmittance was 0.70.7. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0075] Example 5 100 parts by mass of polypropylene (manufactured by Prime Polymer Co., Ltd.: "Y2000G"), 0.5 parts by mass of gallium-doped zinc oxide, and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 230°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (5). The obtained compound (5) was melt-formed into a film at an extrusion temperature of 200°C using a 150 mm wide T-die extruder to obtain an unstretched film (5) for thickness transmittance measurement. Spectroscopic measurement of the obtained film (5) showed that the average transmittance in the visible light region was 76%, the average transmittance in the near infrared region was 66%, and the infrared transmittance / visible light transmittance was 0.90.9. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0076] Example 6 100 parts by mass of polymethylpentene (manufactured by Mitsui Chemicals, Inc.: "TPX (registered trademark) DX820"), 0.5 parts by mass of gallium-doped zinc oxide, and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 280 ° C., mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (6). The obtained compound (6) was melt-formed into a film at an extrusion temperature of 280 ° C. using a 150 mm wide T-die extruder to obtain an unstretched film (6) for transmittance measurement. Spectroscopic measurement of the obtained film (6) showed that the average transmittance in the visible light region was 73%, the average transmittance in the infrared region was 65%, and the infrared transmittance / visible light transmittance was 0.90.9. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0077] Example 7 100 parts by mass of polyethylene terephthalate (manufactured by Unitika Ltd.: "SA-1206"), 0.5 parts by mass of gallium-doped zinc oxide, and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 280°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (7). The obtained compound (7) was melt-formed into a film at an extrusion temperature of 280°C using a 150 mm wide T-die extruder to obtain an unstretched film (7) for transmittance measurement. Spectroscopic measurement of the obtained film (7) showed that the average transmittance in the visible light region was 86%, the average transmittance in the infrared region was 63%, and the infrared transmittance / visible light transmittance was 0.70.7. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0078] Example 8 100 parts by mass of polyamide-6 (UBE Corporation: "UBE NYLON 1013B"), 0.5 parts by mass of gallium-doped zinc oxide, and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 260°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (8). The obtained compound (8) was melt-formed into a film at an extrusion temperature of 260°C using a 150 mm wide T-die extruder to obtain an unstretched film (8) for transmittance measurement. Spectroscopic measurement of the obtained film (8) showed that the average transmittance in the visible light region was 78%, the average transmittance in the infrared region was 59%, and the infrared transmittance / visible light transmittance was 0.80.8. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0079] Example 9 100 parts by mass of polycarbonate (manufactured by Mitsubishi Engineering Plastics Corporation: "Iupilon (registered trademark) S-3001"), 0.5 parts by mass of gallium-doped zinc oxide, and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 280 ° C., mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (9). The obtained compound (9) was melt-formed into a film at an extrusion temperature of 280 ° C. using a 150 mm wide T-die extruder to obtain an unstretched film (9) for transmittance measurement. Spectroscopic measurement of the obtained film (9) showed that the average transmittance in the visible light region was 88%, the average transmittance in the infrared region was 59%, and the infrared transmittance / visible light transmittance was 0.70.7. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0080] Example 10 100 parts by mass of low-density polyethylene, 0.5 parts by mass of gallium-doped zinc oxide, and 0.5 parts by mass of dispersant B (Sigma-Aldrich: sodium polyacrylate, Mw5000, carboxyl group-containing dispersant) were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (10). The obtained compound (10) was melt-formed into a film at an extrusion temperature of 280°C using a 150 mm wide T-die extruder to obtain an unstretched film (10) for transmittance measurement. Spectroscopic measurement of the obtained film (10) showed that the average transmittance in the visible light region was 70%, the average transmittance in the infrared region was 63%, and the infrared transmittance / visible light transmittance was 0.9. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0081] Example 11 100 parts by mass of low-density polyethylene, 0.5 parts by mass of gallium-doped zinc oxide, and 0.5 parts by mass of dispersant C (Kao Corporation: "Polyoxyalkylene alkyl ether sulfate", Mw2000, sulfonic group-containing dispersant) were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (11). The obtained compound (11) was melt-formed into a film at an extrusion temperature of 200°C using a 150 mm wide T-die extruder to obtain an unstretched film (11) for transmittance measurement. Spectroscopic measurement of the obtained film (11) showed that the average transmittance in the visible light region was 72%, the average transmittance in the infrared region was 61%, and the infrared transmittance / visible light transmittance was 0.80.8. The obtained compound was evaluated for aggregates and evaluated for dispersion state as ◯.
[0082] Comparative Example 1 100 parts by mass of low-density polyethylene, 0.5 parts by mass of titanium oxide (manufactured by Teika Corporation: "JR-1000"), and 0.5 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (15). The obtained compound (15) was melt-formed into a film at an extrusion temperature of 200°C using a 150 mm wide T-die extruder to obtain an unstretched film (15) for transmittance measurement. Spectroscopic measurement of the obtained film (15) showed that the average transmittance in the visible light region was 12%, the average transmittance in the infrared region was 13%, and the infrared transmittance / visible light transmittance was 1.1. The obtained compound was evaluated for aggregates as △, and evaluated for dispersion state as ×.
[0083] Comparative Example 2 100 parts by mass of low-density polyethylene and 0.5 parts by mass of gallium-doped zinc oxide were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200°C, mesh filter with a capture particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (16). The obtained compound (16) was melt-formed into a film at an extrusion temperature of 200°C using a 150 mm wide T-die extruder to obtain an unstretched film (16) for transmittance measurement. Spectroscopic measurement of the obtained film (16) showed that the average transmittance in the visible light region was 48%, the average transmittance in the infrared region was 80%, and the infrared transmittance / visible light transmittance was 1.7. The obtained compound was evaluated for aggregates and evaluated for dispersion state, resulting in x.
[0084] Comparative Example 3 100 parts by mass of low-density polyethylene, 20 parts by mass of cesium-doped tungsten oxide, and 20 parts by mass of dispersant A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200°C, mesh filter with a capture particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (18). The obtained compound (18) was melt-formed into a film at an extrusion temperature of 200°C using a 150 mm wide T-die extruder to obtain an unstretched film (18) for transmittance measurement. Spectroscopic measurement of the obtained film (18) showed that the average transmittance in the visible light region was 5%, the average transmittance in the infrared region was 1%, and the infrared transmittance / visible light transmittance was 0.2. The obtained compound was evaluated for aggregates as △, and evaluated for dispersion state as △.
[0085] Comparative Example 4 100 parts by mass of low-density polyethylene, 0.5 parts by mass of gallium-doped zinc oxide, and 1.0 part by mass of dispersant D (manufactured by Aoki Oil & Fat Co., Ltd.: "Brownon SR730", Mw50000, non-ionic dispersant) were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 200°C, mesh filter with a supplementary particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (17). The obtained compound (17) was melt-formed into a film at an extrusion temperature of 200°C using a 150 mm wide T-die extruder to obtain an unstretched film (17) for transmittance measurement. Spectroscopic measurement of the obtained film (17) showed that the average transmittance in the visible light region was 60%, the average transmittance in the infrared region was 77%, and the infrared transmittance / visible light transmittance was 1.7. The obtained compound was evaluated for aggregates and evaluated for dispersion state, resulting in x.
[0086] [Table 1]
[0087] [Table 2]
[0088] [Table 3]
[0089] Example 12 100 parts by mass of polyethylene terephthalate, 0.5 parts by mass of cesium-doped tungsten oxide, and 1.0 parts by mass of polymer A were melt-kneaded in a 30 mmφ twin-screw vent-type extruder (set temperature 280°C, mesh filter with a capture particle size of 20 μm). The obtained thermoplastic resin composition was pelletized to obtain compound (12). The obtained compound (12) and a new thermoplastic resin (d1) (polyethylene terephthalate, manufactured by Far East New Century Co., Ltd.: "CRB-B21SN" (visible light transmittance 89%, average infrared transmittance 88%)) were used, and compound (12) and thermoplastic resin (d1) were simultaneously co-extruded from separate extruders, with compound (12) as the sheath and thermoplastic resin (d1) as the core, with the ratio set to 20 / 80, to produce a core-sheath fiber of 90 dtex 24 f. The produced fiber was used in a knitting machine to produce a weight of 100 g / m. 2 Spectroscopic measurement of the knitted fabric showed that the average transmittance in the visible light region was 81%, the average transmittance in the infrared region was 58%, and the infrared transmittance / visible light transmittance was 0.7.
[0090] Comparative Example 5 Using the compound (12) obtained in Example 12 and a new thermoplastic resin (d2) (titanium oxide dispersed polyethylene terephthalate, manufactured by Far East New Century Co., Ltd.: "CS-910" (visible light transmittance 9%, average infrared transmittance 8%), the compound (12) and the thermoplastic resin (d2) were simultaneously co-extruded from separate extruders, with the compound (12) as the sheath and the thermoplastic resin (d2) as the core, with the ratio set to 20 / 80, to produce a core-sheath fiber of 90 dtex 24 f. The produced fiber was used in a knitting machine to produce a fiber weight of 100 g / m. 2 Spectroscopic measurement of the knitted fabric revealed that the average transmittance in the visible light region was 12%, the average transmittance in the infrared region was 11%, and the infrared transmittance / visible light transmittance was 0.9.
Claims
1. A thermoplastic resin composition comprising a thermoplastic resin (a), a metal oxide (b) and an ionic dispersant (c) as essential components, 90% or more of the metal oxide (b) in the resin composition is present with a size of 500 nm or less, The average transmittance of infrared rays having a wavelength of 1000 to 2000 nm is 70% or less, The average transmittance of visible light having a wavelength of 400 nm to 700 nm is 50% or more, and A thermoplastic resin composition having an infrared transmittance / visible light transmittance in the range of 0.3 to 0.
9. (Note that the size of the metal oxide (b) is a circle equivalent diameter measured by observation with an electron microscope (SEM). Also, 90% or more is a value obtained by counting the number of metal oxide (b) particles that are 500 nm or less among the number of particles of metal oxide (b) present in an area of 100 μm × 100 μm. Also, each average transmittance is a value measured by a method conforming to JIS K 7375 using a test piece with a thickness of 100 μm.)
2. The thermoplastic resin composition according to claim 1 , wherein the metal oxide (b) is an oxide semiconductor.
3. 3. The thermoplastic resin composition according to claim 2, wherein the oxide semiconductor contains at least one selected from the group consisting of molybdenum, nickel, indium, zinc, tin, titanium, vanadium, tungsten, strontium and antimony.
4. The thermoplastic resin composition according to claim 1 or 2, wherein the amount of the metal oxide (b) is in the range of 0.01 to 100 parts by mass per 100 parts by mass of the thermoplastic resin (a).
5. The thermoplastic resin composition according to claim 1 or 2, wherein the thermoplastic resin (a) is at least one selected from the group consisting of polyolefins, polyamides, polyesters, polyarylene sulfides and polycarbonates.
6. The thermoplastic resin composition according to claim 1 or 2, wherein the ionic dispersant (c) has a weight average molecular weight of 20,000 or less.
7. A layer (A) made of the thermoplastic resin composition according to claim 1 or 2; A layer (B) containing a thermoplastic resin (d), The average infrared transmittance of the layer (B) is 60% or more, A thermoplastic resin composite having an average visible light transmittance of 50% or more.
8. A filament, staple, nonwoven fabric, hollow fiber, or film made of the thermoplastic resin composite material according to claim 7.
9. A method for producing a resin composition, comprising a step of blending a thermoplastic resin (a), a metal oxide (b) and an ionic dispersant (c) as essential components, and melt-kneading the mixture at a temperature equal to or higher than the melting point of the thermoplastic resin (a), 90% or more of the metal oxide (b) in the resin composition is present with a size of 500 nm or less, The average transmittance of infrared rays having a wavelength of 1000 to 2000 nm is 70% or less, The average transmittance of visible light having a wavelength of 400 nm to 700 nm is 50% or more, and A method for producing a thermoplastic resin composition having an infrared transmittance / visible light transmittance in the range of 0.3 to 0.
9. (Note that the size of the metal oxide (b) is a circle equivalent diameter measured by observation with an electron microscope (SEM). Also, 90% or more is a value obtained by counting the number of metal oxide (b) particles that are 500 nm or less among the number of particles of metal oxide (b) present in an area of 100 μm × 100 μm. Also, each average transmittance is a value measured by a method conforming to JIS K 7375 using a test piece with a thickness of 100 μm.)
10. The method for producing a thermoplastic resin composition according to claim 9, wherein the metal oxide (b) is an oxide semiconductor.
11. The method for producing a thermoplastic resin composition according to claim 10, wherein the blending amount of the metal oxide (b) is in the range of 0.01 to 100 parts by mass per 100 parts by mass of the thermoplastic resin (a).
12. The method for producing a thermoplastic resin composition according to claim 9, wherein the ionic dispersant (c) has a weight average molecular weight of 20,000 or less.
13. A method for producing a thermoplastic resin composite, comprising a step of melt-molding a resin composition, A layer (A) made of a thermoplastic resin composition produced by the method according to claim 9 or 10; A layer (B) containing a thermoplastic resin (d), The layer (B) has an average infrared transmittance of 60% or more, A method for producing a thermoplastic resin composite having an average visible light transmittance of 50% or more.
14. 9. A method for using the filament, staple, nonwoven fabric, hollow fiber, or film according to claim 8 in swimwear, underwear, fitness wear, protective clothing, fabrics, tents, tarps, umbrellas, and lenses.
15. A molded article obtained by melt molding the thermoplastic resin composition of claim 1 or 2.
16. A method for producing a molded article, comprising the steps of producing a thermoplastic resin composition by the method of claim 9 or 10, and melt-molding the obtained resin composition.
Citation Information
Patent Citations
Clear thermoplastic resin composition and heat-ray- intercepting glazing material prepared therefrom
JP2000234066A
Polycarbonate resin composition and molded article composed the same
JP2011168636A
Infra-red absorption resin composition
JP2016017141A